Perhitungan Harga Pokok Produksi Minuman Kopi Pada Kedai “Hobi Kopi” Kecamatan Ambulu Kabupaten Jember - Sugiarto, Mohammad Alif Dzulkifli; Lestari, Hari Budi; Susanto, Andri Mardi (ACCOUNT (Journal of Accounting and Finance), 2024)
Accurate and precise calculation of the cost of production is very important because the cost of production can provide information in determining selling prices and increasing profits. This research aims to explain the calculation of the Cost of Production (HPP) of drinks at Kedai Hobi Kopi, Ambulu District, Jember Regency. The research method used was a qualitative method and the samples used were 4 best-selling product variants. The results of the research show that calculating the Cost of Goods Production (HPP) using the full costing method has a smaller gross profit value compared to the company's calculations because the company does not calculate production costs in detail, only using Raw Material Costs (BBB) to determine the Cost of Goods Production (HPP). So that the gross profit obtained tends to be greater.